The practicality of smart apps creator-based instructional media on 2D animation subject - Jumaroh Jumaroh; Doni Pernanda; Miftahul Ulum; Chau Trung Tin (Researcher and Lecturer Society, 2023)
Based on the results of observations at Vocational High School Pasundan 1 of Serang City (SMK 1 Pasundan Serang City), some of them do not meet the requirements for mastery learning outcomes, students find it difficult to digest animation lessons, and the teacher's limited ability to make media. Anticipating these obstacles requires an interesting new learning media that can generate students' imagination and creativity, one of which is learning media based on smart app creators. This study aims to find out how the process of developing learning media for Smart Apps Creator, to find out from the development of learning media in 2D Animation subjects that will be used in the learning process and to find out interactive learning media based on Smart Apps Creator in 2D Animation subjects at SMK 1 Pasundan which will be used for the teaching and learning process. This method used Research and Development (R&D). Research through the use of identification of potential and problems, data collection, product design, design validation, revision, product testing, revision, trial, revision and mass production to produce a final product. The trial was conducted on 24 students of class XI SMK Pasundan 1 Serang City. The assessment of the 4 validators of the Interactive Learning Media, which is 90%, shows that the Interactive Learning Media is very valid to be used as a learning resource. The results of the assessment of 24 students that Interactive Learning Media has a practicality value of 89.30%, it can be said that the level of practicality of Interactive Learning Media is very practical and very well stated.